An Ordinance Regarding the Carrying of Concealed Weapons and Sale of Deadly Weapons, THE CONCORDIA WEEKLY DAYLIGHT, May 22, 1888 at 7, § 1. - (:unkn) unknown (General Publisher, 1888)
On and after the passage of this ordinance it shall be unlawful for any person within the city of Concordia to carry upon his or her person any concealed pistol, bowie knife, dirk, sling shot, billy, knuckles, or any other deadly weapon, unless he has a permit to do so.
--
Keywords: CARRY